Edge Computing: Utilization of the Internet of Things for Time-Sensitive Data Processing - Ganapathy , Apoorva (Asian Business Review, 2021)
An edge computing system is a shared IT (Information Technology) system where customer data can be processed at the edge of the network to as close as possible to the originating source. The Internet of Things connects the various things on the internet, making it easier to live and allow jobs to be done more smartly. It also gives total control to the users. The combination of Edge computing and the Internet of Things can potentially result in huge possibilities for users. This work accessed edge computing and the benefits of using edge computing. It also looked into how to edge the many possibilities that can result in the use of edge computing. Various similar concepts like fog and cloud computing were also considered as closely related terms. This article provides insights into the use of edge computing in several industries.